Clinico-epidemiological study of disability due to leprosy at the time of diagnosis among patients attending a tertiary care institution - Vengarakath Puthiyapura Reyila; Ambookken Betsy; Najeeba Riyaz; Sarita Sasidharanpillai; Pentam Veil Beegum Sherjeena; Maniparambath P Majitha; Deepa Mary Joseph (Wolters Kluwer Medknow Publications, 2019)
Background: With the declared elimination of leprosy as a public health problem, the World Health Organization has shifted the focus on the disabilities and deformities associated with leprosy. Aims: The aim was to study the Grade 1 and Grade 2 disability among newly diagnosed leprosy patients. Materials and Methods: All newly diagnosed leprosy patients attending the Outpatient Department of Government Medical College, Kozhikode, from January 1, 2013 to December 31, 2013 were included in the study and the Grade 1 and Grade 2 disabilities observed were analyzed. Results: During the 1-year period, 76 patients were diagnosed to have leprosy. Grade 1 and Grade 2 disabilities were noted in 31.6% and 17.1%, respectively. Major factors identified as risk for leprosy disability at the time of diagnosis were age >45 years, >5 skin lesions, ≥2 thickened peripheral nerve trunks, pure neuritic and borderline tuberculoid spectra of leprosy. Limitation: As the study was conducted in a tertiary care center, it does not perfectly indicate the status in the community. Conclusion: Disability noted in nearly 50% of leprosy cases at the time of diagnosis highlights the need to improve the effectivity of existing health-care system in early case detection and timely referral. In addition, it underscores the need to educate the affected regarding protective eye, foot, and hand care, so that progression to Grade 2 disability can be prevented.